Intergenerational Mobility in Slums: Evidence from a Field Survey in Jakarta - Maisy Wong (Asian Development Review, 2019)
Slums are central to the global debate on inequality, serving as entry points for people moving to cities in search of economic opportunity. Yet we know little about the extent of intergenerational mobility in slums due to a lack of data tracking families across generations (including family members who no longer live together), as well as a lack of data covering slums. This paper addresses these empirical challenges using a field survey of four slums in Jakarta, tracking educational mobility spanning three generations: grandparents, parents, and children. Among grandparents who have less than primary education, only 24% of their children achieve junior secondary schooling or more. By contrast, among parents with less than primary education, 69% of their children attain junior secondary schooling or more. Overall, the patterns suggest improvements in educational mobility across generations. Moreover, there is suggestive evidence that groups with high educational mobility also exhibit high occupational mobility.